Real-life experience with bictegravir/emtricitabine/tenofovir alafenamide in a large reference clinical centre. (19th January 2022) - Ambrosioni, Juan; Rojas Liévano, Jhon; Berrocal, Leire; Inciarte, Alexy; de la Mora, Lorena; González-Cordón, Ana; Martínez-Rebollar, María; Laguno, Montserrat; Torres, Berta; Ugarte, Ainoa; Chivite, Iván; Leal, Lorna; et al.
Abstract: Background: The use of bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) is mainly based on robust, pivotal clinical trials. Objectives: To provide data on clinical use of BIC/FTC/TAF in real life. Patients and methods: This was an observational, retrospective and single-centre study. We included all adult, treatment-naive (TN) and treatment-experienced (TE) people living with HIV (PLWH) starting BIC/FTC/TAF from 8 June 2018. We evaluated effectiveness [on treatment (OT), modified intention-to-treat (mITT) and intention-to-treat (ITT)], tolerability and safety in those patients who reached 6 months of follow-up (M6). Results: We included 1584 PLWH [213 TN (13%) and 1371 TE (87%)]. The median (IQR) follow-up was 16 (7–21) months, with 81% and 53% of PLWH reaching M6 and M12, respectively. By OT, mITT and ITT, HIV-RNA <50 copies/mL was 77%, 70% and 62% at M6 and 92%, 77% and 63% at M12 for TN PLWH and 94%, 89% and 83% at M6 and 93%, 85% and 78% at M12 for TE PLWH, respectively. In PLWH carrying an M184V/I substitution, OT RNA <50 copies/mL was 89.5% at M6. The median CD4 cell count increased from 329 to 511/μL in TN PLWH and from 630 to 683/μL in TE PLWH at M6. Of the total, 1148 (88%) PLWH continued on BIC/FTC/TAF at M6. The most frequent known reason for discontinuation was toxicity [42 (69%) cases]; only 7 cases were considered virological failures (0.6% of the total OT cohort at M6), with no emerging resistance substitutions. Conclusions: In real life, BIC/FTC/TAF showed high rates of virological suppression and also in PLWH carrying lamivudine/emtricitabine resistance substitutions. The tolerability and safety of BIC/FTC/TAF were good, with high persistence observed for patients on this regimen at M6.